The impacts of COVID-19 on migrants, remittances, and poverty in China: A microsimulation analysis - Zhang, Yumei; Zhan, Yue; Diao, Xinshen; Chen, Kevin Z.; Robinson, Sherman (John Wiley & Sons, 2021)
Chinese migrant workers are very exposed to the shocks caused by the COVID-19 pandemic. Falling remittances adversely affect their families who rely on remittance incomes. The impacts of COVID-19 on migrants and remittance-receiving households are assessed using a nationally representative household dataset and a microsimulation model. We found about 70 percent of migrant workers lost part of their wage income during the pandemic lockdown period and rural migrants working in small and medium enterprises were affected the most. This led to about 50 percent of remittance-receiving households being affected adversely by falling remittances, and the average decline in such income was more than 45 percent. Nearly 13 percent of pre-pandemic nonpoor remittance-receiving households could fall into poverty, raising the poverty rate among remittance-receiving households by 4 percentage points. Many households that were poor prior to the pandemic became more impoverished. The results indicate that social protection programs targeting vulnerable migrants and their families at home are important.